MiR-10b-5p is a novel Th17 regulator present in Th17 cells from ankylosing spondylitis. Issue 3 (30th December 2016) - Chen, L; Al-Mossawi, M H; Ridley, A; Sekine, T; Hammitzsch, A; de Wit, J; Simone, D; Shi, H; Penkava, F; Kurowska-Stolarska, M; Pulyakhina, I; Knight, J C; et al.
Abstract : Objective: To determine the microRNA (miR) signature in ankylosing spondylitis (AS) T helper (Th)17 cells. Methods: Interleukin (IL)-17A-producing CD4+ T cells from patients with AS and healthy controls were FACS-sorted for miR sequencing and qPCR validation. miR-10b function was determined by miR mimic expression followed by cytokine measurement, transcriptome analysis, qPCR and luciferase assays. Results: AS Th17 cells exhibited a miR signature characterised by upregulation of miR-155-5p, miR-210-3p and miR-10b. miR-10b has not been described previously in Th17 cells and was selected for further characterisation. miR-10b is transiently induced in in vitro differentiated Th17 cells. Transcriptome, qPCR and luciferase assays suggest that MAP3K7 is targeted by miR-10b. Both miR-10b overexpression and MAP3K7 silencing inhibited production of IL-17A by both total CD4 and differentiating Th17 cells. Conclusions: AS Th17 cells have a specific miR signature and upregulate miR-10b in vitro. Our data suggest that miR-10b is upregulated by proinflammatory cytokines and may act as a feedback loop to suppress IL-17A by targeting MAP3K7. miR-10b is a potential therapeutic candidate to suppress pathogenic Th17 cell function in patients with AS.